Observation and differential cross section measurement of neutral current DIS events with an empty hemisphere in the Breit frame - Andreev, Viktor Konstantinovič; Huber, Florian; Schöning, André (The European physical journal. C, Particles and fields, 2024)
The Breit frame provides a natural frame to analyze lepton-proton scattering events. In this reference frame, the parton model hard interactions between a quark and an exchanged boson defines the coordinate system such that the struck quark is back-scattered along the virtual photon momentum direction. In Quantum Chromodynamics (QCD), higher order perturbative or non-perturbative effects can change this picture drastically. As Bjorken-x decreases below one half, a rather peculiar event signature is predicted with increasing probability, where no radiation is present in one of the two Breit-frame hemispheres and all emissions are to be found in the other hemisphere. At higher orders in $$α _{s}$$or in the presence of soft QCD effects, predictions of the rate of these events are far from trivial, and that motivates measurements with real data. We report on the first observation of the empty current hemisphere events in electron-proton collisions at the HERA collider using data recorded with the H1 detector at a center-of-mass energy of 319 GeV. The fraction of inclusive neutral-current DIS events with an empty hemisphere is found to be $$0.0112 ± 3.9%_\text {stat} ± 4.5%_{\text {syst}} ± 1.6%_{\text {mod}}$$in the selected kinematic region of $$150<Q^{2} <1500\, GeV^2 $$and inelasticity $$0.14<y<0.7$$. The data sample corresponds to an integrated luminosity of 351.1 pb$${}^{-1}$$, sufficient to enable differential cross section measurements of these events. The results show an enhanced discriminating power at lower Bjorken-x among different Monte Carlo event generator predictions.